Ways to Improve the Effectiveness of Depressant Additives for the Production of Winter and Arctic Diesel Fuels; Resources; Vol. 13, iss. 2 - Bogdanov I. A. Ilya Aleksandrovich; Morozova Ya. P. Yana Pavlovna; Altynov A. A. Andrey Andreevich; Titaeva A. M. Alina Maratovna; Kirgina M. V. Mariya Vladimirovna (2024, 2024)
Title screen